Application of Digital Simulation for Training Purposes Through Virtual Reality in The Workplace - Pribadi, Ari Prayogo; Jaladara, Vena; Silalahi, Chris Dwina Anggiana Br; Rahman, Yusuf Mukasyafah Rizqi (The Indonesian Journal of Occupational Safety and Health, 2023)
Introduction: The International Labor Organization (ILO) considers OSH awareness an essential component of OSH training and education. In addition, virtual reality possesses a unique set of characteristics and components and envisaged that by minimizing the risk of accidents during health and safety training. The aim of the research is to further understand the practicality, user experience and efficacy of virtual reality technology in safety education and training. Method: This paper describes and discusses the VR on occupational safety and health. This paper used the Systematic Literature Review to identified 16 articles that are related to VR on occupational safety and health. Articles are written in English and reviews of scientific journals published in the following internet databases; Scopus, SpringerLink, Web of Science, and Wiley Interscience from 2017 to 2023. Results: The incorporation of Virtual reality (VR) into numerous settings has been demonstrated by research conducted on literature reviews. This review found that VR applications can be used to investigate human behavior in dangerous situations in many settings, VR can also be used to create an innovative learning environment in the high-risk sectors, simulate a realistic physical environment and provide experience to enhance knowledge of workplace safety. Moreover, it has been demonstrated that VR has positive impact on learning about increasing OSH awareness. Conclusion: Several studies have shown that virtual reality is one of the most effective training methods at present. It is believed that the application of VR technology could be used to investigate human behavior in dangerous settings; Additionally, VR can be used to improve HSE employers' understanding of unsafe behavior. The VR improves learning about OSH awareness, risk assessment, and recognizing health concerns.